Art and pain in Frida Kahlo - Siqueira-Batista,Rodrigo (2014)
BACKGROUND AND OBJECTIVES: The Mexican painter Frida Kahlo is one of the most important artists of the twentieth century. After being involved in a car accident, remained at home to recover from several injuries, significant event for the dawning of her painting. The aim of this study was to present aspects of the biography and life of Frida, seeking intersections between her artwork and her painful experiences.CONTENTS: From the appreciation of film and screens selected author - analyzed with the support of the articles obtained in the literature review - held four sections to the presentation of evidence obtained: (1) the 'origins' of Frida (2) first accident, (3) the second accident: Diego Rivera and (4) the Martyrdom of frustrated motherhood.CONCLUSION: Frida found in art her comfort, transforming her painful and intense trajectory in a work that reflected the meaning of her existence.